THE DEVELOPMENT OF TESTICLE DIMENSIONS AND BODY GROWTH IN ARABI SHEEP, WITH REFERENCE TO SOME PREDICTION EQUATIONS FOR THESE DIMENSIONS - Mustafa Raisan Kadhim Al Nassar; Zainab S. Alobaidi (European Journal of Agricultural and Rural Education, 2024)
This study was conducted in the fields of the College of Agriculture, University of Basra, for the period from 10/10/2023 to 1/2/2024. The research included a group of Arabi sheep lambs at the ages of 1 to 4 months, and testicle measurements were taken for them at different ages, as the dimensions included both the length and thickness of the testicles. The right and left testicles, the diameter and thickness of the testicles, and the circumference of the testicles were calculated to demonstrate the possibility of relying on these characteristics in selecting males for breeding. It was found that there were significant differences between the ages and different weights of the lambs for the above dimensions. Phenotypic correlation coefficients were also calculated between these characteristics, which were highly significant, high, and positive. Equations were estimated to predict these characteristics based on body weight at early ages, and they all had a high coefficient of determination ranging from 0.83 to 0.91 .